Causes of the Current Stagflation - Grubb, D.; Jackman, R.; Layard, R. (Review of Economic Studies, 1982)
Since 1975 labour slack has been unusually high in the OECD countries, and yet inflation has not diminished. The less favourable mix of unemployment and rate of change of inflation (which we call stagflation) is explained by a fall in the feasible rate of growth of real wages unmatched by a reduction in the constant term in Phillips curve. To investigate this mechanism, conventional wage and price equations are estimated for 19 countries and then used for simulation. Stagflation has been caused in roughly equal amounts by rising relative import prices and by the fall in the rate of productivity growth. In the basic model the Phillips curve is assumed not to adapt to falls in feasible real wage growth, but in a final section an adaptive wage equation is estimated, which confirms that the process of adaptation is slow.